A case for glycerol as an acceptable additive for single‐particle cryoEM samples. Issue 1 (23rd December 2021) - Basanta, Benjamin; Hirschi, Marscha M.; Grotjahn, Danielle A.; Lander, Gabriel C.
Abstract : It is shown that the inclusion of glycerol in single‐particle cryoEM buffers does not preclude high‐resolution structure determination, as demonstrated by an ∼2.3 Å resolution reconstruction of mouse apoferritin (∼500 kDa) and an ∼3.3 Å resolution reconstruction of rabbit muscle aldolase (∼160 kDa) in the presence of 20%( v / v ) glycerol. Abstract : Buffer‐composition and sample‐preparation guidelines for cryo‐electron microscopy are geared towards maximizing imaging contrast and reducing electron‐beam‐induced motion. These pursuits often involve the minimization or the complete removal of additives that are commonly used to facilitate proper protein folding and minimize aggregation. Among these admonished additives is glycerol, a widely used osmolyte that aids protein stability. In this work, it is shown that the inclusion of glycerol does not preclude high‐resolution structure determination by cryoEM, as demonstrated by an ∼2.3 Å resolution reconstruction of mouse apoferritin (∼500 kDa) and an ∼3.3 Å resolution reconstruction of rabbit muscle aldolase (∼160 kDa) in the presence of 20%( v / v ) glycerol. While it was found that generating thin ice that is amenable to high‐resolution imaging requires long blot times, the addition of glycerol did not result in increased beam‐induced motion or an inability to pick particles. Overall, these findings indicate that glycerol should not be discounted as a cryoEM sample‐buffer additive, particularly for large, fragile complexes that are prone to disassembly or aggregation upon its removal.